Paxlovid in Kidney Failure: A Review - Ardianty, Nonie; Suharjono; Hasmono, Didik (Fakultas Farmasi, Universitas Surabaya, 2024)
The COVID-19 virus caused a global pandemic that claimed many lives. Various vaccines and drugs are used for COVID-19 both via intravenous and oral routes. Paxlovid is a treatment given orally to patients who experience symptoms and is even considered effective in reducing high-risk COVID-19 virus infections. Kidney failure is a special population that can worsen COVID-19. The purpose of this review article was to determine the effectiveness and safety of using Paxlovid in patients who have comorbid diseases, one of which is kidney failure. The method used in preparing this journal was the PRISMA diagram to select the right articles and Google Scholar, Pubmed, and ScienceDirect as literature sources. Based on the exclusion and inclusion criteria, around 4 studies were obtained that were appropriate to the research topic. Paxlovid may be an important option to reduce the risk of COVID-19 in at-risk patients and unvaccinated patients, moreover, careful consideration of the benefits and risks to patients can be reviewed.